PERAN INDIVIDU, KELUARGA, DAN MASYARAKAT DALAM PENANAMAN NILAI-NILAI DAN KARAKTER ISLAMI PADA ANAK - Masitoh, Dewi (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This study aims to discuss how the role of individuals, families, and communities in instilling Islamic values and characters in children. Researchers use literature studies using a qualitative approach, which is research that does not use quantitative data calculations. The main or primary literature studied in this study is scientific journals and Islamic Education literature. The results of this study state that individuals, families and communities play an important role in instilling Islamic values and characters in children